NON-MONETARY INCENTIVES PREFERENCES AS MOTIVATIONAL TOOL OF NEWLY APPOINTED SALES PERSONNEL OF SOFT DRINK INDUSTRY - Yeop Yunus, Nek Kamal; MG, Arsalan; Abdul Malik, Muhammd; Khan, Naveed Ur Rehman (International Business Education Journal, 2014)
Motivated employees are the substantial assets of any organization. Newly appointed employees’ behavior set the tune of an organization’s future. So their motivation is an important point to concentrate on for firms’ decision maker. This study is a new dimension of the research of Malik et al. (2011), in which newly appointed sales personnel preferences revealed about non-monetary incentive (NMI) as a motivational tool. In this study, the importance of factors of non-monetary benefits like security, social NMI, tangible NMI, relations with peers their effects on motivation of newly appointed sale force of the soft drink industry of Karachi, Pakistan. The findings suggested that, most preferred NMI (ranking wise) for newly appointed sales personnel is tangible non-monetary incentives, job related, non-monetary incentives, security, relations with peers and social non-monetary incentives. One interesting finding of the study is consistent with Malik et al. (2011) that newly appointed sales personnel also prefer the monetary benefits to non-monetary benefits.